New PGA UMP leadership appointed - Shahrizai, Sarif (2023)
KUANTAN, 2 February 2023 - The Institute of Postgraduate Studies (IPS) Universiti Malaysia Pahang (UMP) held the UMP 2023 Postgraduate Association Appointment Ceremony and UMP 2022 Postgraduate Association Appreciation Ceremony at the AC Mariott Kuantan Hotel.